Analisis Kebijakan Penerapan E-SAMSAT Pembayaran Pajak Kendaraan Bermotor dalam meningkatkan Pendapatan Asli Daerah - Habibah Nurul Fitri; Rahma Nazilla Muhammad; Mia Rosmiati (Jurusan Akuntansi Politeknik Negeri Bandung, 2021)
This study aims of this research is to find out how policy the implementation of E-SAMSAT payment of motor vehicle tax (PKB) to increase the locally generated revenue (PAD) and the obstacles they face. This is a descriptive research with qualitative and data sources from both primary and secondary data. The techniques of data collection used documentation and interview studies with the Miles and Huberman models as data analysis techniques. The results of the study found that policy the implementation of E-SAMSAT PKB payments could increase PAD viewed from the dimensions of communication, resources, disposition, and bureaucratic structure in general is good. This is evidenced by an increase in PKB revenues in 2016-2019, which resulted in an increase in PAD. However, the obstacles experienced by E-SAMSAT both internally and externally in its implementation still often occur. These obstacles include the mismatch data, double transactions, inappropriate data input, system failure, validation of STNK which still has to be done at the SAMSAT office, the community those who are not literate with the technology, public doubts about the validity of E-SKKP, and the socialization has not been distributed.